The effect of emergency department occupancy on the revisitation rate within seven days among patients discharged by triage - Jari Ylä-Mattila; Anna Eidstø; Jalmari Nevanlinna; Heini Huhtala; Teemu Koivistoinen; Sami Mustajoki (BMC Emergency Medicine)
Abstract Background Emergency department (ED) crowding has been repeatedly shown to affect patient outcomes negatively. However, there is limited research on its impact on patients immediately discharged by the triage team. This study aimed to evaluate the effect of ED occupancy level on the rates of ED revisitation and hospitalization within seven days among patients discharged or redirected by the triage team. Methods An observational single-center study was conducted at the Tampere University Hospital ED from January 1, 2023, to December 31, 2024. The study population consisted of patients who were discharged or redirected by the ED triage team. These patients were divided into two groups: (1) patients who revisited the ED within seven days and (2) patients who did not return within seven days. A subgroup analysis focused on revisits that resulted in hospitalization. ED occupancy at the time of triage was considered as a predicting factor for revisitation and hospitalization. Age, sex, triage shift, and the updated Charlson Comorbidity Index (uCCI) were adjusted for in a multivariable logistic regression analysis. Results Of the 180,267 ED visitors during the study period, 8.8% (n = 15,910) were discharged by the triage team. Of these, 8.7% (n = 1392) revisited the ED within seven days, and 16.2% (n = 225) of the revisiting patients were hospitalized. In the multivariable analyses, the highest quartile of ED occupancy was associated with an increased likelihood of ED revisitation (odds ratio [OR]: 1.29, 95% confidence interval [CI]: 1.06–1.57). Older age was linked to both revisitation and hospitalization (OR for a 1-year increase 1.01 [95% CI: 1.01–1.02] and 1.02 [95% CI: 1.02–1.03], respectively). The uCCI score was also associated with revisitation and hospitalization (OR for a 1-point increase 1.13 [95% CI: 1.07–1.18] and 1.23 [95% CI: 1.13–1.33], respectively). Conclusions The highest ED occupancy quartile was associated with a modestly increased likelihood of an ED revisit but not hospitalization within seven days after being discharged by the triage team. Furthermore, age and comorbidities were associated with both revisitation and hospitalization. Trial registration Clinical trial number: not applicable.